Daptomycin for methicillin-resistant Staphylococcus epidermidis native-valve endocarditis: a case report - Duah Marylene (BMC, 2010)
Abstract Coagulase-negative staphylococci (CoNS) have been increasing in importance as a cause of native valve endocarditis (NVE). Most cases of NVE caused by CoNS are attributable to Staphylococcus epidermidis. NVE caused by CoNS acquired in a nosocomial setting may differ from cases acquired in the community in several ways. It may be associated with hemodialysis, the presence of a long-term indwelling central catheter or pacemaker, or a recent invasive procedure; nosocomial cases may have a higher rate of methicillin resistance among CoNS isolates, and so be more likely to be treated with vancomycin. Unfortunately, NVE caused by methicillin-resistant CoNS has been associated with significantly higher rates of persistent bacteremia and in-hospital mortality than methicillin-susceptible isolates. The poor outcomes in these cases point to the need for alternative therapies with potent activity against methicillin-resistant CoNS. In our medical center, a 76-year-old man presented with native-valve endocarditis and positive blood cultures for methicillin-resistant Staphylococcus epidermidis (MRSE). During each of three 6-week courses of treatment with vancomycin, blood cultures were negative, but they once again became positive for MRSE when vancomycin was discontinued. The minimum inhibitory concentration of the MRSE isolates for vancomycin remained stable at 2 μg/mL. Eventually, treatment with daptomycin was initiated (500 mg [7 mg/kg]) 3 times/week for 6 weeks. Over the following year, no positive cultures for MRSE were detected.